ALKALI-ACTIVATION OF FLY ASH/MIRHA BLEND IN GEOPOLYMER CONCRETE FOR IN-SITU APPLICATION - KUSBIANTORO, ANDRI (2012)
Geopolymer is a recently-developed material for civil engineering structure. In general, geopolymer comprises alkaline solution and amorphous source material. Dissolution of geopolymer precursors from source material is accelerated with the presence of alkaline solution. The combination of NaOH and Na2SiO3 as the alkaline solution is providing a faster dissolution and polycondensation rate in geopolymer system. Nevertheless, in fly ash based geopolymer concrete, elevated temperature is required to increase the geopolymer reaction kinetics hence rapid production of geopolymer gel is not interrupted. The utilization of electric equipment to supply the required heat has limited the utilization of geopolymer concrete to be in pre-cast application only. Therefore, alternative curing methods, i.e. hot gunny, ambient, and external exposure, were studied to overcome the kinetic reaction issue and extend the utilization of geopolymer technology to the in-situ application. In addition to the source material character, microwave incinerated rice husk ash (MIRHA) is a state of the art pozzolanic material that contains high amount of reactive silica.